(untitled) (Journal of the Institute of Engineering, 2018)
The Ranjana script, which is also known as Kutila or Lantsa, is one of the many alphabets derived from the Brahmi script. This numesmetic inscription was developed 2216 years ago, so its time period was along the 199 BC and it was popular from 11th century AD and was used until the mid-20th century in Nepal and India. It is popularly used by Nepali in the Newari language. This script also known as Lantsa, for writing the Sanskrit titles of books which have been translated from Sanskrit to Tibetan for decoration in temples and mandalas. There were few texts printed with alternating lines in Sanskrit in the Lantsa script followed by a Tibetan translation. There were many original Sanskrit manuscripts written in Lantsa preserved in Newar community in Nepal. Others were destroyed lack of its preservation. In addition, the Ranjana script was used mainly for decoration by Buddhists. Journal of the Institute of Engineering, 2017, 13(1): 221-224